Reproductive tissue expression and sperm localization of porcine beta-microseminoprotein - Maňásková-Postlerová, Pavla; Davidová, Nina; Sulc, Miroslav; Philimonenko, Anatoly; Hozák, Pavel; Jonáková, Věra (Cell and tissue research, 2011)
Beta-microseminoprotein (MSP) is a predominant protein of human seminal plasma and originates from prostate secretions. MSP from boar seminal plasma has been sequenced and shows only 50%-52% homology with that of human. Porcine MSP is synthesized by the post-natal prostate gland and is identical with the sperm motility inhibitor. Although MSP is a protein characteristic of the prostate gland, we have established the presence of its mRNA transcript not only in boar prostate but also in other reproductive organ tissues. In extracts of all these organs, specific polyclonal antiMSP antibody recognizes a 12-kDa protein band identified by mass spectrometry as MSP. Immunofluorescence (IMF) has revealed the occurrence of MSP in the epithelial tissue of the prostate, epididymis, seminal vesicles and Cowper's glands. MSP has been localized on epididymal spermatozoa in the acrosomal region and on the flagellum of ejaculated spermatozoa. The absence of MSP on the surface of capacitated spermatozoa together with the antibody detection of MSP in the sperm acidic extract after in vitro capacitation indicates its acrosomal origin. Additionally, MSP has been localized by IMF in the sperm acrosome in capacitated spermatozoa with a permeabilized plasma membrane and by electron microscopy in ejaculated spermatozoa. The function of MSP in seminal plasma and spermatozoa is not fully understood. Nevertheless, the secretion of porcine MSP by various reproductive organs indicates its multiple roles in the reproductive process. For the first time in mammalian species, MSP has been localized in various physiological stages of sperm.
Keywords: Microscopy, Electron; Seminal Vesicles; fluorescenční protilátková technika; Male; lidé; Molecular Sequence Data; hmotnostní spektrometrie; Spermatozoa; sekvence aminokyselin; Fluorescent Antibody Technique; Humans; Prostatic Secretory Proteins; Semen; sperma; prasata; Mass Spectrometry; elektronová mikroskopie; semenné váčky; Animals; akrozom; sekreční proteiny prostaty; Acrosome; zvířata; mužské pohlaví; prostata; spermie; messenger RNA; Swine; Prostate; Amino Acid Sequence; molekulární sekvence - údaje; RNA, Messenger